Long-Term Outcome after Vitrectomy for Macular Edema with Retinal Vein Occlusion Dividing into the Occlusion Site - Takeshi Iwase; Brian C. Oveson (Journal of Ophthalmology)
Purpose. To investigate the efficacy of treatment for macular edema secondary to retinal vein occlusion (RVO) with vitrectomy. Methods. This retrospective study identified patients with macular edema associated with RVO between January 2004 and April 2006. Inclusion criteria were eyes with (1) preoperative visual acuity (VA) of 20/40 or worse, (2) a central foveal thickness (CFT) greater than 250 μm, and (3) vitrectomy with internal limiting membrane and intravitreal triamcinolone acetonide. Each patient had their RVO classified as a major or macular BRVO or hemispheric RVO (HSRVO). Results. Forty-six eyes with major BRVO, 18 eyes with macular BRVO, and 17 eyes with HSRVO were investigated. VA was significantly improved at 24 months after surgery for each group (P<0.05). Vision in the macular BRVO group 24 months after surgery was significantly better than that in other groups (P<0.05). For each group, a concomitant reduction of CFT was noted at every time point when compared to preoperative values (P<0.001). Conclusions. In macular BRVO, the postoperative vision 24 months after surgery was significantly better than the other groups. These findings suggest that additional and earlier treatments might be more important for patients with major BRVO and HSRVO than for those with macular BRVO.